PENGARUH KOMUNIKASI TENAGA FARMASI DALAM UPAYA PENINGKATAN PEMAHAMAN LANSIA TERHADAP DAGUSIBU OBAT (DAPATKAN, GUNAKAN, SIMPAN, BUANG) DI DESA KOPEN KABUPATEN BOYOLALI - Anisawati, Amanda; Isma, Faizatul; Tansa, Ilham La; Hanifah, Rafidah; Diana, Rizky Nur; Santoso, Aris Prio Agus (Jurnal Riset Kefarmasian Indonesia, 2021)
Irrational use of drugs and their abusers is a problem that is often found in society. Based on the survey data obtained, there are still residents who get drugs freely without monitoring medical and pharmaceutical personnel or the drugs purchased are medicines from grocery stores, and many residents in Kopen village, Boyolali, do not know how to use appropriate drugs and how to store them. The correct medicine and many of them are still throwing away liquid medicine in the package and without paying attention to damage the medicine package. Education about the drug Dagusibu is one of the efforts we do as pharmaceutical personnel to prevent irrational drug use and to prevent drug abuse by the community, especially the elderly in Kopen Village, Boyolali. The method used is a preventive intervention method and a quantitative approach to the elderly using the Dagusibu questionnaire that we created. Based on filling out the questionnaire before we do the socilization, it was found that 73% of the elderly who do not understand, 18% of the elderly who have little understanding and 7% of the elderly who are accompanied by a guardian who already understands. The understanding of Dagusibu drugs by the elderly in the Village Kopen, Boyolali categorized't get it. It needs to be held socialization to improve the understanding of the elderly and also residents in the Village kopen, Boyolali. After socialization, the obtained results of the questionnaire 27% still do not understand, 64% already understand and also 9% are elderly, accompanied by a guardian in the use of the drug. The conclusion of this research is the role of pharmaceutical personnel hold a very important role in conveying information and education in an improved understanding of the elderly and residents in the Village kopen, Boyolali..